Peran Guru Dalam Penanaman Nilai Karakter Disiplin Pada Siswa Melalui Pembiasaan Sekolah: The Role Of The Teacher In Instrumenting The Character Value Of Discipline In Students Through School Habituation - Dwi Priastuti; Santy Dinar Permata; Uci Ulfa Nur’afiffah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Based on preliminary observation school habituation activities at Luqman Al Hakim Ngawi Elementary School were carried out well. Teachers and students are involved in these habituation activities. This is an interesting concern for research to find out the implementation of school habituation activities as a means of instilling disciplinary character values in students. The purpose of this study was to determine the teacher's role in instilling the character values of discipline in students through school habituation activities. This study used qualitative research with a case study approach. The data sources in this study were school principals, 3 teachers, and 24 students using data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques in this study used interactive data analysis techniques data collection, data condensation, data display, and conclusions. Research result conducted in school habituation activities to instill discipline character values in students, it is known that the teacher acts as a catalyst who invites, directs, and supervises students in school habituation activities. The teacher also acts as a role model who provides an example for discipline to students. Based on the research result above the existence of the role of the teacher in carrying out the school habituation can instill the character values of discipline in students.